Penanaman Sikap Melalui Sosialisasi Anti Perundungan Dan Kekerasan Seksual SDN 1 Ploso Nganjuk - Putri, Adinda Firsa Amartya; Nur Faizahain; Luthfi Rosyida; Dhita Ayu Permata Sari; Moh. Danang Bahtiar (Universitas Negeri Surabaya, 2024)
Knowledge about bullying and sexual violence in educational settings is a challenge that must be considered. Bullying is an act of using power to hurt a person or group in a verbal, physical or psychological form, so that the victim is traumatized, depressed, depressed and helpless. Meanwhile, sexual violence is an act of sexual harassment against someone without the consent of the party concerned. The problem at SDN 1 Ploso is the lack of attention and knowledge of students about bullying and sexual violence. Through outreach activities at SDN 1 Ploso, Nganjuk District, Nganjuk Regency, it is hoped that 70 students will be able to obtain information about bullying and sexual violence, so that in the future students will not commit and be able to avoid bullying and sexual violence at school and outside of school. This socialization stage is carried out through planning, implementation and evaluation. Keywords: Socialization, Bullying, Sexual Violence